Deep river - Endō, Shūsaku 1923-1996 (New Directions, 1994)
In India, four Japanese tourists converge on the River Ganges in search of absolution. The novel probes their consciences, from Isobe, grieving the death of the wife he ignored in life, to Kugachi, haunted by wartime memories of a man who saved his life by eating human flesh, then drank himself to death to forget. An analysis of the importance of religion